COLLABORATION OF MARINE ECOTOURISM IN RIAU ISLANDS PROVINCE TOWARDS SUSTAINABLE TOURISM - Alfiandri, Alfiandri; Prasojo, Eko; Salomo, Roy Valiant (Advances in Social Sciences Research Journal, 2021)
The purpose of this study is to analyze the existence of collaborative governance in the development of marine ecotourism in a sustainable manner in Bintan Regency, Riau Islands Province using a collaborative governance model approach. This study uses a qualitative approach, where the researcher performs one stage of qualitative data collection at a time, simultaneously (concurrently). This research is useful for increasing basic knowledge about the relationship between marine ecotourism development institutions, and also enriching the knowledge base, especially in the field of public administration. Besides, this research does not provide practical applications that can be applied in the short term but can become a basis for knowledge in solving problems and making policies related to improving institutional relations between institutions in the development of marine ecotourism. Then, it can be implemented by stakeholders and also the Regional Government of Bintan Regency in the development of sustainable marine ecotourism. The collaborative institutional strengthening model has an important role in building community involvement. This model can strengthen network systems and information flow and reduce disagreements between stakeholders. An important role in the development of local indigenous-based tourism potential, not only in the role of the central or regional government but also the role of all actors in the tourism community who have an important role in developing sustainable tourism.